2015
DOI: 10.1016/j.juro.2015.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of the Pippi Salle Procedure for Intractable Urinary Incontinence in Patients with Severe Intrinsic Urethral Sphincter Deficiency

Abstract: Although we experienced some minor complications in the short term, most patients were simply and successfully treated with endoscopic surgery. The long-term results of the Pippi Salle procedure are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Nakamura et al (38) reported results of the Salle procedure in 12 children (9 with NSBD) Seven were completely dry (58%) at a mean follow-up time of 75 months. Three had experienced difficulties with urethral catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…Nakamura et al (38) reported results of the Salle procedure in 12 children (9 with NSBD) Seven were completely dry (58%) at a mean follow-up time of 75 months. Three had experienced difficulties with urethral catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence in SCI patients is insufficient for establishing specific recommendations. In the series of Nakamura et al, [6] one female SCI patient with severe intrinsic urethral sphincter deficiency achieved complete dryness in the long run. In the total group difficulty of catheterizing through the urethra (25%), and urinary calculi (8%) were complicating factors.…”
Section: Bladder Neck Reconstructionmentioning
confidence: 94%
“…The original technique described by Young-Dees-Leadbetter was modified in recent decades by different urological surgeons mainly in pediatric patients with bladder extrophy [206,[211][212][213][214]. These techniques provide continence rates of 50-94% [206,207,211,215,216]. However, such bladder neck/urethral reconstructions require regular ISC to empty the bladder and often prior or simultaneous bladder augmentation to secure low pressure storage [217].…”
Section: Bladder Neck/urethral Reconstructionmentioning
confidence: 99%